The polymorphisms (rs3213801 and rs5744533) of DNA polymerase kappa gene are not related with glioma risk and prognosis: A case‐control study. (8th October 2019) - Wu, Ying; Zhou, Linghui; Deng, Yujiao; Li, Na; Yang, Pengtao; Dong, Shanshan; Yang, Si; Zheng, Yi; Yao, Li; Zhang, Ming; Zhai, Zhen; Dai, Zhijun; et al.
Abstract: DNA polymerase kappa ( POLK ), one of the specialized Y family DNA polymerases, functions in translesion synthesis and is suggested to be related with cancers. Single nucleotide polymorphisms (SNPs) in specialized DNA polymerases have been demonstrated to be associated with cancer risk. To evaluate the association of two common POLK variants (rs3213801 C>T and rs5744533 C>T) with glioma, we conducted a case‐control study and genotyped these two POLK variants in 605 patients and 1300 healthy controls. The association analysis revealed no significant correlations were observed between these two POLK SNPs and glioma risk. However, the POLK rs3213801 CT genotype was found to be higher in older glioma patients (≥40) than in younger patients ( P  = .026). Compared with patients harboring the CC genotype, the frequencies of POLK rs5744533 CT and CT+TT genotypes were increased in patients with lower World Health Organization (WHO) grade glioma ( P  = .028, 0.044, respectively). According to Kaplan‐Meier analysis and log‐rank tests, POLK SNPs were not correlated with either the overall survival or progression‐free survival. Nevertheless, multivariate analysis revealed that the age (≥40) could increase the risk of death in glioma patients ( P  < .05), while gross‐total resection and temozolomide treatment were found to play protective roles in glioma prognosis ( P  < .001, respectively). Overall, our results indicated that POLK variants rs3213801 and rs5744533 are not associated with glioma risk and prognosis. However, these polymorphisms are likely to be associated with certain glioma characteristics, such as age and WHO grade. The age, surgery types, and chemotherapy could be independent prognostic factors in glioma. More studies are required to confirm our findings. Abstract : In this study, we found DNA polymerase kappa variants rs3213801 and rs5744533 are not associated with glioma risk and prognosis, but they are likely to be associated with certain glioma characteristics, such as age and World Health Organization grade. Meanwhile, the age, surgery types, and chemotherapy could be independent prognostic factors in glioma.